2000
DOI: 10.30843/nzpp.2000.53.3614
|View full text |Cite
|
Sign up to set email alerts
|

Autumnapplied urea and other compounds to suppress <i>Venturia inaequalis</i> ascospore production

Abstract: The effect of urea applied to apple leaves in autumn on production of ascospores of Venturia inaequalis (black spot) was quantified in four studies. Autumn urea at concentrations from 0-20% reduced ascospore production in spring in proportion to the log of the urea concentration. A single application of 5% urea sprayed onto fallen leaves gave an 88% decrease in ascospore production. Urea applied to apple trees before leaf fall significantly reduced black spot disease on leaves the following spring in cv. Fuji,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…The differences in numbers of ascospores trapped at the two experimental sites were probably due to the different climates at the two sites, since the periodicity of rainfall causes differences in ascospore maturation and release (MacHardy 1996). The significant effect of the nutrient amendment urea, which caused a 77% reduction overall in ascospore numbers in this trial, agreed with those from other field trials, in which urea reduced ascospore numbers by 65-95% in England (Burchill 1968) and 88% in New Zealand (Beresford et al 2000). However, Bio-Start™ was ineffective despite the leaf decomposition effects described in recent European trials (G. Besamusca, pers.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The differences in numbers of ascospores trapped at the two experimental sites were probably due to the different climates at the two sites, since the periodicity of rainfall causes differences in ascospore maturation and release (MacHardy 1996). The significant effect of the nutrient amendment urea, which caused a 77% reduction overall in ascospore numbers in this trial, agreed with those from other field trials, in which urea reduced ascospore numbers by 65-95% in England (Burchill 1968) and 88% in New Zealand (Beresford et al 2000). However, Bio-Start™ was ineffective despite the leaf decomposition effects described in recent European trials (G. Besamusca, pers.…”
Section: Discussionsupporting
confidence: 89%
“…Application of nitrogenous compounds has also been found to reduce primary inoculum of apple black spot. Many authors have reported the beneficial effects of autumn applications of urea (Burchill 1968;Carisse et al 2000;Beresford et al 2000). Ross & Hamlin (1965) reported that nitrate and ammonium salts, and amino acids were equally effective to urea, completely preventing development of pseudothecia.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to black spot control, the higher the autumn urea application rate, the greater the suppression of ascospore production (Beresford et al 2000). However, application rates of 2-5% urea, which in these studies were shown to avoid bud damage, can still give substantial ascospore suppression and are therefore useful for black spot management.…”
Section: Discussionmentioning
confidence: 86%
“…Urea applied to apple trees during leaf fall suppresses the production of ascospores of the black spot fungus (Venturia inaequalis) the following spring and is an important component in the management of black spot in New Zealand apple orchards (Beresford et al 2000). The closer to leaf fall that urea is applied, the more effective the suppression of ascospore production, and therefore 2-3 urea applications are often made during leaf fall.…”
Section: Introductionmentioning
confidence: 99%
“…Many growers are using postharvest foliar urea applications as a way to ensure that bud reserves of N are high, even when added fertilizer N is being reduced with the goal of increasing crop quality (Sánchez et al, 1995). There is also some evidence that a postharvest urea application increases leaf decay rates and reduces the incidence of disease the following year (Beresford et al, 2000;Burchill, 1968). It is important to determine whether B can be added effectively to a postharvest foliar urea application, thus eliminating the need for a B application the following spring.…”
Section: Methodsmentioning
confidence: 99%